Roles of 1-phosphatidylinositol 3-kinase and ras in regulating translocation of GLUT4 in transfected rat adipose cells. - Quon, M J (1995)
Insulin stimulates glucose transport in insulin target tissues by recruiting glucose transporters (primarily GLUT4) from an intracellular compartment to the cell surface. Previous studies have demonstrated that insulin receptor tyrosine kinase activity and subsequent phosphorylation of insulin receptor substrate 1 (IRS-1) contribute to mediating the effect of insulin on glucose transport. We have now investigated the roles of 1-phosphatidylinositol 3-kinase (PI 3-kinase) and ras, two signaling proteins located downstream from tyrosine phosphorylation. Rat adipose cells were cotransfected with expression vectors that allowed transient expression of epitope-tagged GLUT4 and the other genes of interest. Overexpression of a mutant p85 regulatory subunit of PI 3-kinase lacking the ability to bind and activate the p110 catalytic subunit exerted a dominant negative effect to inhibit insulin-stimulated translocation of epitope-tagged GLUT4 to the cell surface. In addition, treatment of control cells with wortmannin (an inhibitor of PI 3-kinase) abolished the ability of insulin to recruit epitope-tagged GLUT4 to the cell surface. Thus, our data suggest that PI 3-kinase plays an essential role in insulin-stimulated GLUT4 recruitment in insulin target tissues. In contrast, over-expression of a constitutively active mutant of ras (L61-ras) resulted in high levels of cell surface GLUT4 in the absence of insulin that were comparable to levels seen in control cells treated with a maximally stimulating dose of insulin. However, wortmannin treatment of cells overexpressing L61-ras resulted in only a small decrease in the amount of cell surface GLUT4 compared with that of the same cells in the absence of wortmannin. Therefore, while activated ras is sufficient to recruit GLUT4 to the cell surface, it does so by a different mechanism that is probably not involved in the mechanism by which insulin stimulates GLUT4 translocation in physiological target tissues.